Protecting Nature in a “Legal in Nature” Seventh Amendment Framework: Reimagining EPA Enforcement Post-Jarkesy - Chu, Bertrand (Columbia Journal of Environmental Law, 2026)
In Securities and Exchange Commission v. Jarkesy, the Supreme Court held that defendants accused of securities fraud were entitled to jury trials under the Seventh Amendment, and that the SEC could not adjudicate these cases before their expert administrative law judges.Worryingly, this case implicates the Environmental Protection Agency, whose enforcement strategy similarly relies on internal adjudication. This Note proposes various legal and policy solutions that mitigate the impacts of Jarkesy to preserve the critical work of the EPA in protecting the health, safety, and environment of the American public. First, the EPA can attempt to distinguish itself from the SEC through the public rights exception, and through the statutory language that empowers its enforcement. Second, the EPA can emphasis non-traditional forms of environmental redress that do not involve penalties that implicate the Seventh Amendment. Finally, the EPA can engage with state actors to fill in potential gaps in federal enforcement. While the current Supreme Court seems determined to declaw administrative agencies, alternative means remain for the EPA.